Cellular structure design based on free material optimization under connectivity control - Hu, Jingqiao; Li, Ming; Yang, Xingtong; Gao, Shuming (Computer aided design, 2020)
Cellular structures exhibit exceptional multifunction performance at relatively low densities and have wide industrial applications, but their effective design still remains challenging. The study aims to find a manufacturable cellular structure of valid geometry under certain volume usage budget, given a fixed design domain under external loadings. It is achieved via first introducing the concept of free material optimization (FMO), which provides an ultimately best structure among all possible elastic continua. After this, two novel control strategies are developed in combination with inverse homogenization to ultimately produce a cellular structure of valid geometric connectivity. It mainly includes approaches of material space reduction via hierarchical clustering, and a novel physics-based connectivity control to tailor the geometric connectivity between neighboring microstructures. Performance of the approach is tested on various 2D examples, in comparison with structures generated via classical (multiscale) topology optimization approaches. [Display omitted] •Manufacturable cellular structure optimization on FMO field.•Hierarchical clustering to reduce material space while maintaining physical fidelity.•Physics-based geometric connectivity control between neighboring microstructures.•Comparisons in depth with benchmark results.